Hygienic risk assessment for humans from consuming vegetables contaminated with difenoconazole-based fungicides - Stavnichenko, Pavlo; Merezhkina, Nataliia (The Ukrainian Scientific Medical Youth Journal, 2025)
One of the key directions for increasing agricultural crop yields is the use of chemical plant protection products, particularly pesticides. Considering the growing use of these products due to intensive cultivation technologies, the study of pesticide persistence in agricultural crops is of great importance for maintaining product quality and safety. Uncontrolled use of these substances may negatively affect human health, especially when employed for treating agricultural products. The aim of our study was to carry out a hygienic risk assessment for humans consuming vegetables contaminated with a difenoconazole-based fungicide. Materials and methods of the study included determining the content of the triazole-class compound, difenoconazole, in vegetable crops (tomatoes, cucumbers, carrots, potatoes, cabbage) in various soil and climatic zones of Ukraine. The persistence of the fungicide in different vegetable crops was evaluated, and the values of its half-life period (τ50) and near-total degradation period (τ95) were calculated. The assessment of pesticide hazards was carried out using an integral hazard index in consumption of pesticide-contaminated products, classified into four categories ranging from low hazardous to extremely hazardous. Statistical processing of the results was performed using the software packages MedStat v.5.2 (Copyright © 2003-2019), Microsoft® Excel® for Microsoft 365 MSO (version 2305, build 16.0.16501.20074), and Python 3.11. The half-life (τ50) of difenoconazole in the studied agricultural crops was 9.51±0.67 days on average. It should be noted that the τ50 was significantly the shortest in potatoes, with a value of 5.9±0.55 days (95% CI 4.5-7.31), compared to other vegetable crops. A comparison of the obtained results with published data from other countries showed that the half-life periods of difenoconazole in vegetable crops are comparable and fall within acceptable intervals. The calculated stability parameters (τ50) allowed difenoconazole to be classified as belonging to Hazard Class III in all the studied crops (SSanN&R 8.8.1.002-98). When assessing the integral hazard index in consumption of pesticide-contaminated products (IHIPC) of difenoconazole on human health, it was found that when consuming contaminated agricultural products, the studied fungicide belonged to hazard сlass III. The obtained results should be taken into account when considering the possibility of expanding the use of difenoconazole-based fungicides to ensure human safety and the effectiveness of application on various plants.